Self-excited asynchronous generator with PV array in detained autonomous generation systems - Karthikeyan Nagarajan; Anbarasi Jebaselvi Gnanaiah David (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
It's important to examine and handle the issue of green energy generation in inaccessible locations. Nonrenewable hybrid power has environmental and economic impacts. Reliable electricity and energy efficiency are priorities. Renewable energy that is eco-friendly and doesn't affect the environment. Solar and wind power, two ecologically benign and load-sharing-capable forms of renewable energy, are included in this technique. At the same time, solar power will keep the load voltage balanced and the system stable thanks to the inclusion of a DC-DC converter. The asynchronous generator has been selected because of its low maintenance needs and extended service life; nevertheless, the voltage on the load side is unbalanced when this machine is in operation. An asynchronous generator can be a viable alternative to well-developed synchronous generators for use in wind turbines or small hydro generators because they have relatively inexpensive costs, are simple, require inadequate maintenance, possess adequate resistance to wear and tear, and have reduced overload damage. It is difficult to maintain a continuous supply of energy in faraway regions because of the lack of related work in the power distribution networks. This problem is addressed in this paper by a well-designed converter that maintains a constant output voltage.